Dyslipidaemia in Schizophrenia (Anwer Khan Modern Medical College Journal, 2021)
Background: Lipid neurochemistry is an important focus in schizophrenia research. Disorder of fatty acid metabolism within the brain tissue play an important role in the pathophysiology of schizophrenia.Material & Methods: To evaluate the association of dyslipidaemia with Schizophrenia and compare the serum lipid profile with healthy individuals, a cross sectional analytical study was conducted between July 2011 and June 2012 in the Department of Biochemistry, Dhaka Medical College, following approval of a protocol. As per criteria, total 100 cases were included in this study and divided into two groups: Group-I (Diagnosed cases of schizophrenia) and Group-II (Healthy individuals). Written informed consent was taken from all cases. Serum lipid profile (Total Cholesterol, Triglycerides, HDL and LDL) was estimated from both groups by enzymatic determination.Result: Fasting serum triglyceride (p